Ilioprofunda Endobypass Can Successfully Treat a Post-Operative Femoral Pseudo-Aneurysm. (2017) - Mehta, T.; Dey, R.; Chaudhuri, A.
Abstract : Introduction: A 75-year-old male patient with significant cardiopulmonary comorbidity presented with a 70-mm left femoral pseudoaneurysm 6 years after aortobifemoral bypass (and prior femoral endarterectomy). Report: As the left superficial femoral artery was occluded, an ilioprofunda endobypass was undertaken following extraperitoneal exposure of the left limb of the bypass graft with subsequent deployment of four Viabahn endoprostheses via the left limb into the proximal left deep femoral artery with successful exclusion of the pseudoaneurysm. The endografts remain patent at 6 months with regression noted in the pseudoaneurysm itself. Discussion: Post-operative femoral pseudoaneurysm following anastomotic dehiscence has traditionally been treated by open surgical repair. Re-re-do open femoral vascular surgery has a high complication rate. Scarring and potential graft infection may necessitate ligation of involved arteries and extra-anatomic bypasses with an attendant risk of limb loss. Although the common femoral artery is conventionally contraindicated for endograft deployment because of the perceived high risk of stent fracture in a highly mobile zone, an endobypass can avoid the potential complications of open revision groin surgery in an unfit, high-risk patient. Highlights: Femoral pseudoaneurysm in re-do vascular surgery background. Femoral artery endovascular repair.